Cytotoxicity Test of Cocoa Bean Extract (Theobroma cacao L.) Fermented and Unfermented Edel Varieties Against Human Gingival Fibroblast Cells - Nihla Fitriyani; Rina Sutjiati; Yuliana Mahdiyah Da'at Arina (Health Notions, 2021)
Cocoa beans are one of the most widely developed herbal plants, one of which is edel cocoa beans. Processing of cocoa beans can be through a fermentation process or not. The fermentation process can significantly reduce the concentration of total polyphenols and other active components in cocoa beans through oxidation and exudation processes. Cocoa beans are one of the plants that are rich sources of polyphenols. These polyphenols, especially flavonoids, have various benefits against several pathological disorders, such as cardiovascular disease, inflammatory processes, and cancer. In dentistry, cocoa bean extract gel has been shown to increase the number of fibroblast cells in the socket after tooth extraction of male Wistar rats, so that it has potential as a therapeutic agent. The requirement for a material to be used as therapy is that it must be safe and non-toxic, so it is necessary to carry out a biocompatibility test to ensure safety for the human body.Keywords: toxicity; fibroblast cells; cocoa bean extract